Europe, the Green Island? Developing an integrated energy system model to assess an energy-independent, CO2-neutral Europe - Broghan Helgeson (Institute of Energy Economics at the University of Cologne (EWI), 2024)
The paper at hand offers a quantitative assessment of the transformation of the European energy system in achieving the goal of the European Commission of carbon neutrality in Europe by 2050. In doing so, the investment and dispatch optimization model DIMENSION is extended to comprise a greater number of sectors and technologies as well as endogeneous links between energy supply and demand for 28 countries in Europe up to 2050. The model is applied to examine the cost- minimal decarbonization pathway for two scenarios with varying spatial boundaries of the optimization, namely the Green Island Europe and Green Importer Europe scenarios: Whereas the consumption of green hydrogen and/or synthetic fuels in the Green Island Europe scenario requires an investment in the necessary power-to-x production and electricity generating capacities within Europe, the Green Importer Europe scenario allows for such zero-carbon and carbon-neutral fuels to be available for purchase from outside of Europe. Results of the cost minimization in both scenarios show that the model chooses to most rapidly decarbonize the electricity sector, with capacities of wind and solar electricity generation in Europe tripling between 2019 and 2030. Simultaneously, a 500 TWhel increase in electricity demand is observed as 77% of heat generation in Europe is supplied by electricity-consuming heating technologies in 2030. By 2050, flexibility options such as electricity storage, demand-side management and electric vehicles expand their market presence, while the more hard-to-abate sectors such as transport and industry experience a rapid shift from fossil fuels to biofuels as well as to green hydrogen. As a result, the cross-sectional European CO2 shadow price rises to 225 exteuro/tCO2 in 2040 and to 559 exteuro/tCO2 in 2050. In the Green Island Europe scenario, carbon neutrality in an energy-independent Europe leads to an overall increase in electricity consumption in Europe of over 4000 TWhel between 2019 and 2050. Yet the long-term results of the two scenarios diverge as the emergence of a demand for green hydrogen leads to a diversification of Europe's hydrogen supply, with approximately 300 TWhth of green hydrogen (19% of total consumption) imported from outside of Europe in 2050. In turn, the 250 TWhth decrease in domestic green hydrogen production leads to a ramping down of electrolysis systems in the Green Importer Europe scenario, creating an opportunity for other flexibility options. Finally, the difference in average consumer and producer surplus as well average total welfare between the scenarios is examined for players in the European electricity and green hydrogen markets.
Keywords: C61; C68; D61; N70; Q41; Q42; Q48; 330; Energy system modeling; Flexibility options; Electricity sector; Power-to-x; Green hydrogen; Synthetic fuels; Green fuels; Sector coupling; Decarbonization; Carbon neutrality; Energy independence; Security of supply; Welfare analysis